The steadfastness of the Algerian Female Mujahideen, stories and testimonies from the liberation revolution1956-1962 - Yahiaoui, Abdelwahab; bensilette, Mostefa (The Algerian Historical Journal, 2026)
The Algerian liberation revolution began in circumstances where the French colonialism intensified, and no one excluded from it .Neither Men, women, elders non children’s ,that was enough to recruit all of them, against the enemy ,as the Algerian martyr EL ARBI BEN M’hidi said “ throw the revolution to the street people will adopt it.The Algerian woman, just like men, she welcomed the revolution with passion and she realized that she must be on her brother’s side to get the freedom and the national sovereignty. She responded to the national front liberation call and joined the revolution she did her national duty perfectly in all the domains: The political military social and the cultural domains, She was a soldier, a militant, a nurse and a guide; she endured the worst psychological torture.